let x1 and x2 be the roots such that:

x1= 1- sqrt3

x2= 1+sqrt3

Then ( x-x1) and (x-x2) are factors of the function :

==> f(x) = [x - (1-sqrt3)] [ x - (1+sqrt3)]

= (x -1 + sqrt3) (x-1 - sqrt3)

Now let us expand the brackets:

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

let x1 and x2 be the roots such that:

x1= 1- sqrt3

x2= 1+sqrt3

Then ( x-x1) and (x-x2) are factors of the function :

==> f(x) = [x - (1-sqrt3)] [ x - (1+sqrt3)]

= (x -1 + sqrt3) (x-1 - sqrt3)

Now let us expand the brackets:

= x^2 - x - sqrt3*x - x + 1 + sqrt3 + sqrt3*x - sqrt3 - 3

Reduce and group similar terms:

= x^2 - 2x - 2

**==> f(x)= x^2 - 2x -2 **